Noma in northwest Nigeria: a neglected disease in neglected populations - Farley, Elise Sarah (Department of Public Health and Family Medicine, 2021)
Background Noma, also known as cancrum oris, is a gangrenous infection of the oral cavity, which causes widespread orofacial destruction. If untreated, noma has a reported 90% mortality rate within weeks after the onset of first symptoms. Noma progresses through distinct stages defined by the World Health Organisation (WHO); Stage 0: simple gingivitis; Stage 1: acute necrotizing gingivitis; Stage 2: oedema; Stage 3: gangrene; Stage 4: scarring. Stage 5: sequelae. It is unclear how many patients with the early stages of noma will progress to the later stages of disease. Treatment in the early reversible stages with antibiotics, wound debridement and nutritional support greatly reduces morbidity and mortality. Acute noma is most often reported in children aged between two and five years. Many patients who survive the acute stages of the disease suffer into adulthood with disfigurement and disability of varying degrees. Noma is thought to be most prevalent in developing countries in Africa and Asia. Estimates for noma prevalence and incidence vary. In 1998, the WHO estimated an annual incidence of 140,000 cases of acute noma and 770,000 noma survivors living with sequelae. Two Nigerian studies estimated the burden of disease ranged from seven cases per 1,000 children aged between one and 16 years (2003) to 6.4 per 1,000 children (2003). A study from 2019 estimated the period prevalence of noma from 2010 to 2018 was 1.6 per 100,000 population at risk in Nigeria. These estimates are based on expert opinion, number of hospital admissions and retrospectively collected hospital-based data and it is unclear which stages of noma were included. Risk factors for the disease include poor oral hygiene, malnutrition, comorbidities and low socioeconomic status. Despite its ancient history (reported by Hippocrates (460 - 370 BC)), noma-related literature remains mainly confined to case reports and case series. By employing both qualitative and quantitative methods, we sought to examine the biopsychosocial features of noma, its epidemiology and treatment in northwest Nigeria in order to inform advocacy and prevention efforts. The three overarching objectives to fulfil this aim were to assess the distribution of noma among children in northwest Nigeria; identify factors associated with noma (including factors influencing health-seeking behaviour and risk factors for the development of noma) and gain an understanding of the biomedical and non-biomedical care provided to noma patients in this setting. The knowledge gained through this thesis will support the assessment of the need for advocacy around noma, effective resource allocation and the planning of intervention strategies. Methods We conducted a scoping literature review, three quantitative studies (risk factors, outcomes, prevalence) and two qualitative studies (language and beliefs and traditional healing practices) in northwest Nigeria. Data were collected from patient caretakers at the Noma Children's Hospital, hospital staff, children and traditional healers in villages within Sokoto and Kebbi States. Data collection methods included quantitative surveys, oral screenings, anthropometric measurements, quality of life questionnaires, qualitative in-depth interviews and focus group discussions. Consenting adult respondents answered questionnaires and participated in interviews, and where applicable, data was collected from assenting children. Quantitative analyses included descriptive statistics as well as univariable and multivariable risk factor analyses. Qualitative data was manually coded and analysed thematically. Findings We included 74 cases (noma patients presenting at the hospital in the year preceding data collection) and 222 controls (both median age of five years (inter-quartile range 3, 15 years)) in the risk factor study. Vaccination coverage for polio and measles was below 7% in both cases and controls. The multivariable analysis identified the child being fed pap every day (adjusted odds ratio (aOR) 9.8; 95% confidence interval (CI 1.5, 62.7) as a risk factor. The mother being the primary caretaker (aOR 0.08; CI 0.01, 0.5) and the caretaker being married (aOR 0.006; CI 0.0006, 0.5) were protective factors. Of the 37 patients with noma sequelae included in the outcomes study, 21 (56.8%) were male and 22 (62.9%) were aged six years or older. Fifteen patients (40.5%) had two to three surgeries. The most frequently used surgical procedure was a deltopectoral flap (n=16 patients; 43.2%). Trismus was released in 12 patients (32.4%), of these; none had a normal mouth opening at the follow-up visit. Despite this finding, all respondents reported that the surgery had improved their quality of life. In the cross-sectional study assessing the prevalence of all stages of noma, we included 3,499 households and 7,122 children aged <15 years; 4,239 (59.8%) were aged 0 to 5 years. Simple gingivitis was identified in 3.1% (n=181; CI 2.6-3.8), acute necrotizing gingivitis in 0.1% (n=10; CI 0.1-0.3), and oedema in 0.05% (n=3; CI 0.02-0.2). No cases of late-stage noma were detected. Naming of the disease differed between caretakers and healthcare workers in the language and beliefs study. Beliefs about the causes of noma were varied (spirits, animals, insects, previous infections). Noma patient caretakers spoke of the mental health strain due to stigmatization as a key issue. Difficulty in accessing care was evident. A lack of trust in the health system was mentioned as a barrier to care. Traditional healers offered specialised forms of care for specific conditions and referral guidance. They viewed the stages of noma as different conditions with individualised remedies and were willing to refer noma patients. Caretakers trusted traditional healers. Conclusion Social conditions and childhood feeding practices are associated with the occurrence of noma in northwest Nigeria. This thesis has shown that following their last surgical intervention, noma patients do experience some improvements in their quality of life, but continue to face functional challenges that inhibit their daily life. We found many, widely distributed, early-stage noma cases in northwest Nigeria indicating a large population at risk of progressing to the later stages of disease. Caretaker and practitioner perspectives may enlighten efforts to improve case finding, and to understand barriers to accessing health care. Differences in disease naming illustrated the difference in beliefs about the disease. Traditional healers could play a crucial role in the early detection of noma and the health-seeking decision-making process of patients. Intervention programmes should include traditional healers through training and referral partnerships. In conclusion, this thesis provides a unique view of the biopsychosocial features, epidemiology and treatment options for noma in northwest Nigeria. Noma is a disease, which is indicative of a weak health system and socio-economic environments of extreme deprivation. Intervention programmes should include widespread health system improvements that could address a host of risk factors for noma, and simultaneously other childhood diseases. These include increasing access to quality health care (including vaccinations), ensuring effective referral mechanisms, predominantly in rural areas, and the creation of a robust surveillance network. Health financing initiatives would need to be paired with these improvements. Nutritional programs aimed at caretakers of young children and community-based oral health initiatives could be effective mechanisms to curb the number of noma cases. Awareness-building initiatives targeting healthcare workers and community members are necessary to improve the detection and timely management of noma in endemic settings. The combined findings of this thesis highlight the neglected nature of noma and make a strong case for placing noma on the WHO neglected tropical diseases list. This initiative could foster awareness among policy-makers and governments and direct much needed funding to facilitate further research, surveillance and targeted health interventions that would contribute to the eradication of noma.